Calculation of the environmental capacity of cooling ponds for cage fish farming - N. Starco (Ribogospodarsʹka Nauka Ukraïni, 2016)
Purpose. The determination of a maximum annual amount of fish reared in cagesm which does not result in the deterioration of the ecological state of water cooling ponds of the Zmiev Thermal Power Plant and Kursk Nuclear Power Plant series Ι and ΙΙ.